A pilot field evaluation on heat stress in sugarcane workers in Costa Rica: What to do next? - Van Wendel de Joode, Berendina (2009)
Climate change is producing major impacts including increasing temperatures in tropical countries, like Costa Rica, where the sugarcane industry employs thousands of workers who are exposed to extreme heat. Objectives: This article outlines a pilot qualitative evaluation of working conditions and heat in the sugarcane industry. Design: A literature review, direct observations and exploratory interviews with workers were conducted to reach a preliminary understanding of the dimensions of heat-related health issues in the sugarcane industry, as a basis for the design of future studies. Results: The industry employs temporary workers from Nicaragua and Costa Rica as well as year-round employees. Temporary employees work 12-hour shifts during the harvest and processing ('zafra') season. In many cases, sugarcane field workers are required to carry their own water and often have no access to shade. Sugar mill workers are exposed to different levels of heat stress depending upon their job tasks, with the most intense heat and workload experienced by the oven ('caldera') cleaners. Conclusions: Research is needed to achieve better understanding of the multiple factors driving and interacting with heat exposures in the sugarcane industry in order to improve the health and safety of workers while maintaining worker productivity. © 2009 Jennifer Crowe et al.